3D-Reconstruction of the Complex Stuccoes from Patrimony Buildings - Rodica-Mariana Ion; Valentin Gurgu; Ioan Alin Bucurica; Sofia Teodorescu; Mihaela-Lucia Ion; Dana Postolache; Ioan Darida (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2017)
The paper deals with 3D scanning techniques and instruments to survey the complex stuccoes from the architectural building Nanu-Muscel from Bucharest. EXAscan Portable 3D Laser Scanner has been used to exploit the advantages of the 3D surveying techniques and produce digital models and other geometric representations useful for the protection of historic architectures and a correct solution for their restoration. After the parameterization, the scanning of two stucco-objects surface yielded to a network of points. The program analyzes the points and joins them, so the final result being the scanned object in electronic format (digitized), by "Digitized Shape Editor" module in the Catia program. The not useful surfaces have been removed and for the symmetrical reconstruction the mirroring operation was applied.